Personality and mental health changes throughout the course of university police training in Sweden - Mehdi Ghazinour; Mojgan Padyab; Lars-Erik Lauritz; Jörg Richter (Nordisk Politiforskning, 2019)
Abstract Police trainees have to be prepared for future job demands and challenges. Personality plays an important role in stress management. The first assessment of a longitudinal investigation was conducted among 103 Swedish police trainees to study their personality changes and mental health responses in first two weeks after intake. Fifty-two of these trainees, who participated in the second assessment, were included in the analysis. The Temperament and Character Inventory (TCI) was used to measure personality, and the Symptom Checklist-90-Revised (SCL-90-R) was used to measure mental health. A multiple regression analysis was performed with personality scores from the first assessment as independent variables and SCL-90-R scores as dependent variables. Over two years, minor changes were found in the police trainees’ personality characteristics, which seemingly fit the demands of policing and are potentially valuable in the trainees’ future careers. Personality characteristics are predictors of mental health at the end of university training.